Seismic demand on column splices in special concentrically braced frames - Faytarouni, Mahmoud; Şeker, Onur; Akbaş, Bülent; Shen, Jay (Elsevier Sci Ltd, 2019)
Given the lack of comprehensive research on seismic demands on column splices in special concentrically braced frames (SCBFs), this study presents an inclusive investigation on splice demands in SCBFs to address whether the seismic design requirements for column splices in AISC Seismic Provisions are conservative or not. The study numerically evaluates the nonlinear response of 5-story and 13-story SCBFs with common two-story X -bracing configuration under an ensemble of strong earthquake ground motions. For each SCBF, two structural models were considered to examine the impact of shifting column splice locations on splice demands. The study concludes that flexural demands on column splices exceed the minimum required flexural design strength stipulated in the seismic provisions for the column splices in SCBFs. The likelihood of reaching the nominal capacity of the smaller column is very high for column splices under combined effects of axial force and bending moment, indicating an unsatisfactory margin of safety against the excessive inelastic deformations expected to take place in ductile braced frames.
Keywords: Seismic demands; Column splices; Concentrically braced frames; Non-linear time history analysis; Column splice location; Splice tensile demands; Splice flexural demands; Splice shear demands